Two-photon microscopic imaging of capillary red blood cell flux in mouse brain reveals vulnerability of cerebral white matter to hypoperfusion. Issue 3 (March 2020) - Li, Baoqiang; Ohtomo, Ryo; Thunemann, Martin; Adams, Stephen R; Yang, Jing; Fu, Buyin; Yaseen, Mohammad A; Ran, Chongzhao; Polimeni, Jonathan R; Boas, David A; Devor, Anna; Lo, Eng H; et al.
Despite the importance of understanding the regulation of microvascular blood flow in white matter, no data on subcortical capillary blood flow parameters are available, largely due to the lack of appropriate imaging methods. To address this knowledge gap, we employed two-photon microscopy using a far-red fluorophore Alexa680 and photon-counting detection to measure capillary red blood cell (RBC) flux in both cerebral gray and white matter, in isoflurane-anesthetized mice. We have found that in control animals, baseline capillary RBC flux in the white matter was significantly higher than in the adjacent cerebral gray matter. In response to mild hypercapnia, RBC flux in the white matter exhibited significantly smaller fractional increase than in the gray matter. Finally, during global cerebral hypoperfusion, RBC flux in the white matter was reduced significantly in comparison to the controls, while RBC flux in the gray matter was preserved. Our results suggest that blood flow in the white matter may be less efficiently regulated when challenged by physiological perturbations as compared to the gray matter. Importantly, the blood flow in the white matter may be more susceptible to hypoperfusion than in the gray matter, potentially exacerbating the white matter deterioration in brain conditions involving global cerebral hypoperfusion.